E-selectin Targeting PEGylated-thioaptamer Prevents Breast Cancer Metastases - Yoshihiro Morita (Molecular Therapy: Nucleic Acids, 2016)
E-selectin is an adhesion molecule expressed on the luminal surface of inflamed blood vessels that mediates hematogenous metastasis by assisting shear-resistant adhesion of circulating tumor cells to the vessel surface under dynamic blood flow. Previously, we developed an E-selectin antagonistic thioaptamer (ESTA) for the prevention of hematogenous metastasis through the blockade of CD44high breast cancer cells (BCa) adhesion to E-selectin-expressing premetastatic endothelial niche. The current study focuses on developing a PEGylated E-selectin targeting thioaptamer with improved pharmaceutical properties. A serial deletion of stem-loops reveled that loop-1 and -2 (ESTA7) are the minimally effective backbone structure necessary to obtain inhibition of the E-selectin/CD44 interaction and shear resistant adhesion of CD44high BCa to E-selectin-expressing human endothelial cells (HMVECs) at a level equal to ESTA. Chemical conjugation of methoxy-polyethylene-glycol (PEG) at the sizes of 5 and 10 kDa did not interfere with ESTA7-mediated shear-resistant adhesion. However, in vivo study demonstrated that only 10 kDa PEG-conjugated ESTA7 (ESTA7-p10) retains the activity to inhibit metastases at a level equal to parental ESTA. Additionally, a single intravenous injection of ESTA7-p10 inhibited the development of lung, brain, and bone metastases of MDA-MB-231, through the blockade of E-selectin. Moreover, PEGylation led to an extension of elimination half-life and increase of AUC, resulting in superior inhibition of metastasis development compared to parental ESTA with a longer interval between dosing in a spontaneous metastasis model. Lastly, repeated intravenous administration of ESTA7-p10 was tolerated in mice, highlighting the potential prophylactic application of ESTA7-p10 for metastasis prevention.